Mild Neonatal Brain Hypoxia-Ischemia in Very Immature Rats Causes Long-Term Behavioral and Cerebellar Abnormalities at Adulthood - Sanches, Eduardo Farias; van de Looij, Yohan; Toulotte, Audrey; Sizonenko, Stéphane Vladimir; Lei, Hongxia (Frontiers in Physiology, 2019)
Systemic hypoxia-ischemia (HI) often occurs during preterm birth in human. HI induces injuries to hinder brain cells mainly in the ipsilateral forebrain structures. Such HI injuries may cause lifelong disturbances in the distant regions, such as the contralateral side of the cerebellum. We aimed to evaluate behavior associated with the cerebellum, to acquire cerebellar abundant metabolic alterations using in vivo1H magnetic resonance spectroscopy (1H MRS), and to determine GFAP, NeuN, and MBP protein expression in the left cerebellum, in adult rats after mild early postnatal HI on the right forebrain at day 3 (PND3). From PND45, HI animals exhibited increased locomotion in the open field while there is neither asymmetrical forelimb use nor coordination deficits in the motor tasks. Despite the fact that metabolic differences between two cerebellar hemispheres were noticeable, a global increase in glutamine of HI rats was observed and became significant in the left cerebellum compared to the sham-operated group. Furthermore, increases in glutamate, glycine, the sum of glutamate and glutamine and total choline, only occurred in the left cerebellum of HI rats. Remarkably, there were decreased expression of MBP and NeuN but no detectable reactive astrogliosis in the contralateral side of the cerebellum of HI rats. Taken together, the detected alterations observed in the left cerebellum of HI rats may reflect disequilibrium in the glutamate-glutamine cycle and a delay in the return of glutamine from astrocytes to neurons from hypoxic-ischemic origin. Our data provides in vivo evidence of long-term changes in the corresponding cerebellum following mild neonatal HI in very immature rats, supporting the notion that systemic HI could cause cell death in the cerebellum, a distant region from the expected injury site. HIGHLIGHTS - Neonatal hypoxia-ischemia (HI) in very immature rats induces hyperactivity toward adulthood. - 1H magnetic resonance spectroscopy detects long-term cerebellar metabolic changes in adult rats after neonatal HI at postnatal day 3. - Substantial decreases of expression of neuronal and myelin markers in adult rats cerebellum after neonatal cortical mild HI.